IMPACT OF THE COVID-19 PANDEMIC ON THE DENTAL EMERGENCY DEPARTMENT SERVICE PATTERN: EXPERIENCE OF A UNIVERSITY-BASED DENTAL HOSPITAL IN INDONESIA - Eka Pramudita Djimantoro; Riznasyarielia Nikmatun Nafisah; David Buntoro Kamadjaja (Dentino: Jurnal Kedokteran Gigi, 2026)
Background: The COVID-19 pandemic and the policies taken by the Indonesian government have had a major impact on health sectors and resulted in changes in health services patterns provided by the Emergency Department (ED) in dental hospitals. Identifying changes in dental hospital visits is pivotal to formulate policies that must be prepared immediately and adapted to the dynamics for the use of dental and oral health service during pandemic. Objective: This study compares services at the ED of the Universitas Airlangga Dental Hospital during the pre-pandemic and the beginning of the COVID-19 pandemic.Method:This is a retrospective study, based on data extracted from the medical records of all patients who came to the ED during March-July 2019 and the COVID-19 period (March-July 2020). Patients were classified according to the case diagnosis, and the data of the two periods were statistically compared using the independent t-test or the Mann-Whitney U test, as applicable. Results:There was an increase in the number of patient visits in March-July 2020 (503 patients) compared to March-July 2019 (113 patients). The highest number of visits was in April 2020 (143 patients). Infection and miscellaneous cases were the most common in both periods with drastic increase in 2020. There were significant differences in the total number of visits, infections, and miscellaneous cases.Conclusion: The COVID-19 pandemic in Indonesia has caused a change in the general picture of dental and oral health services by an increase in patient number and case distribution.Keywords:COVID-19, Dental hospital, Emergency department, Health service, Pandemic